Memorialization of the Holocaust in Transylvania during the early post-war period. Issue 2 (3rd April 2017) - Tibori-Szabó, Zoltán
Abstract: Details of the fate of the Jewish community in Northern Transylvania, under Hungarian state administration after 1940, were of common knowledge already by the last months of the Second World War. Consequently, wide circles of the local population could have been familiar with its nature and events. However, only the top members of the political and church elites were aware about the tragedy of the Transylvanian Jews after their deportation. Between 1945 and 1949, the Transylvanian media presented several times the most important facts of the horrors of the Holocaust. Simultaneously, the surviving members of the annihilated Northern Transylvanian Jewish communities did everything in their power to immortalize the memory of the tragedy in literary and art works. During the decades of communist consolidation, when all areas of social life, the facts of the Holocaust included, fell under the reign of silence, these early creations of Holocaust memorialization played an important role in keeping the memory of the genocide alive and constantly directing the attention of young generations upon the sinister legacy of Nazism and fascism.